L’Atlantique de l’esclavage, 1775‑1860. - Marie-Jeanne Rossignol (Transatlantica)
Although slavery was condemned in France, Britain, and the United States from the 1770s to the 1790s, leaders in all three countries considered that as a first step the international slave trade should be abolished. Britain was particularly active in promoting an international campaign against the trade after 1807, mainly by diplomatic means. This led to a spate of declarations and treaties in the 1810s and 1820s, and to a general agreement in Western countries on how unacceptable and criminal the importation of enslaved Africans was. However the now illegal trade picked up after 1820 due to a growing demand for labour in plantation societies in the Americas. Nationalist concerns clashed with humanitarian goals on the Atlantic, hindering real international police efforts. Most ambiguous in its commitment to ending the transatlantic slave trade was the United States : not only did it not repress the trade but American entrepreneurs were often involved in the transatlantic operations. The point of the paper is to examine this gradualist period in the history of antislavery, insisting on its international and comparative dimension, while underlying the peculiar position of the United States in the antebellum period.